Video-Assisted Thoracoscopic Surgery (VATS) in the Treatment of Pulmonary Bulla - Rahman , S M Tajdit; Rahman Mia, Md Mofizur; Hossain, Mosharraf; Islam Shakil , Kazi Saiful; Kibria, Anwarul Anam; Biswas, Manabendra; Rahim, Abdur; Hossain , Mobarak; Islam , Md Nazmul; Razzaque , A K M Razzaque (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction: Video-assisted thoracoscopic surgery (VATS) has been widely applied for the treatment of intrathoracic diseases, including bullous lung disease. VATS has been evaluated to replace thoracotomy for various lung resection surgeries. This study aims to determine the efficacy, safety, and outcome VATS for bullectomy. Method: This retrospective study was performed from January 2021 to December 2022 in the department of Thoracic Surgery at National Institute of Diseases of the Chest & Hospital, Dhaka and Green Life Hospital, Dhaka. We reviewed all the patients who underwent bullectomy through VATS within this period. The demographic and operative variables were collected. The safety and efficacy of the procedure in terms of postoperative complications and change in lung function after bullectomy was analysed. Result: Forty patients underwent elective VATS bullectomy due either to giant bulla or pneumothorax. Among them, 36 were male with mean age 47.4 years (range 20-65 years). There was significant improvement in lung function following bullectomy. Approximately one third patients (32.5%) developed postoperative complications, majority having air leak. There was no postoperative mortality within 30 days. Conclusion: VATS resection is a safe and effective treatment for bullous lung disease with significant improvement in symptoms and lung function following surgery. J Bangladesh Coll Phys Surg 2023; 41(4): 287-293